(untitled) (Via Litterae (ISSN 2176-6800): Revista de Linguística e Teoria Literária, 2013)
The construction of masculinities for the African diaspora has been an issue from slavery times until today. In the play Elmina's Kitchen, by Kwame Kwei-Armah, the construction of masculinities for the black community in England is contested from the perspective of three different generations of black men, either Caribbean immigrants or British-born men. It is possible to use the obstacles they face and their responses to them to shape the common problems presented to black men to achieve their manhood as well as their usual responses to such obstacles. Moreover, this play emphasizes the role of violence in the construction of black masculinities in view of their symbolical castration by white society and by their own peers, as well as the importance of the black woman in the patching of black men's wounds and mending of black families.